The geobiology and ecology of metasequoia - International Metasequoia Symposium (1st : 2002 : Wuhan, China); LePage, Ben A.; Williams, Christopher J. (Christopher James), 1970-; Yang, Hong (Dordrecht : Springer, 2005)
42